CHML promotes liver cancer metastasis by facilitating Rab14 recycle - Tian-Wei Chen (Nature Portfolio, 2019)
Metastasis-associated recurrence is a major cause of poor prognosis in hepatocellular carcinoma. Here, the authors show that expression of choroideremia-like (CHML) is elevated and associates with poor prognosis in hepatocellular carcinoma, and mechanistically CHML promotes metastasis in a Rab14-dependent manner.